(untitled) (Indian Journal of Animal Production and Management, 2017)
An investigation was carried out to determine the effects of various condiments (mint, curry leaves and green chilli @ 2.50% paste) and salt concentrations (1.00%, 1.25%, 1.50% and 2.00%) on proximate, microbiological and sensory attributes of yoghurt spread. Yoghurt was prepared with NCDC 263 culture. Significant differences were observed between the condiments used in respect of total solids (TS) (P<0.001), moisture (P<0.001), protein (P<0.01) and fat (P<0.05) of the product. Salt concentrations, however, had a significant difference only on ash content (P<0.001). The average pH and titratable acidity (TA) of yoghurt spread were 4.80 and 0.411% lactic acid (LA), respectively. The total aerobic count of the samples proportionately decreases with increase in salt concentration. Tucky’s HSD test showed significant impact of interaction between the condiments and salt concentration with respect to all sensory parameters. Superior overall ratings for yoghurt spreads containing Curry Leaves with 1.50% salt concentration is reported.